A community-based father education intervention on breastfeeding practice in Ethiopia: a quasi-experimental study - Wolde Melese Ayele; Tesfaye Birhane Tegegne; Asnakew Molla Mekonen (BMC Pediatrics)
Abstract Background Breastfeeding is the cornerstone of a newborn’s nutrition, containing crucial nutritional components. While a substantial body of research focuses on mothers, there is limited understanding regarding effective strategies to engage fathers in promoting breastfeeding practices. Therefore, this quasi-experimental study investigated a community-based intervention to improve breastfeeding exclusivity and initiation rates by targeting fathers in breastfeeding education. Methods This research was conducted in Dessie City in the Amhara region of Northeast Ethiopia from 5th October 2020 to 30th August 2021. Fathers and their wives were assigned individually to the intervention and control groups. Baseline data were gathered from selected Kebeles (Kebele: the lowest administrative level in Ethiopia) to identify couples seeking care through routine maternal and child health services. Fathers in the intervention area received breastfeeding education services at health facilities or home visits during antenatal, delivery, and postpartum periods. Trained midwives participated in giving breastfeeding education. In the control arm, they received routine counseling activities. Factors associated with early initiation and exclusive breastfeeding were analyzed using multivariable analysis among the two groups. Results The intervention involved 327 participants, 155 in the intervention arm and 172 in the control group. The multivariable analysis indicated that the community-based father health education intervention significantly influenced the early initiation of breastfeeding. Mothers in the intervention group were found to be nearly five times more likely to initiate breastfeeding within the first hour of their infants’ lives (AOR: 4.85, 95% CI: 1.36—17.32). A significant positive impact was also found for exclusive breastfeeding (EBF) of infants at the 1st, 4th, and 6th months (AOR: 3.95, 95% CI: 1.09—14.27), (AOR: 5.47, 95%CI: 2.18—13.70), and (AOR: 1.70, 95% CI: 1.02—2.85) respectively. Conclusion This study confirmed the positive effects of a community-based father education intervention on the rates of exclusive breastfeeding during the first, fourth, and sixth months, as well as the early initiation of breastfeeding. The government and healthcare workers should implement policies supporting father-inclusive breastfeeding initiatives such as creating awareness and the critical role fathers’ play.